Spillovers espaciais de criminalidade na região integrada para desenvolvimento do Distrito Federal e entorno: uma análise de crimes contra a pessoa e contra o patrimônio - Silva, Luciano Pereira da (2020)
The discussion on crimes in the field of Geography has a vast literature, whose debates permeate several dimensions: social, spatial, economic, demographic, among others. However, a common denominator in the discussions about crime is its connection with the phenomena of industrialization and urbanization. Therefore, the theoretical discussion of this work began by assuming crime as an urban issue, and the overall objective of the thesis consisted in understanding the spatial distribution of crime in the Integrated Network for the Development of the Federal District (RIDE/DF), as well as their relations with socio-spatial conditions. The theoretical literature review focused on the ideas of the Chicago School in which they report that the acceleration of urbanization triggered in major world centers by industrialization, caused several social illnesses due to the lack of decent conditions of urban life related and the poor offer of urban infrastructure, which induce a weakening of community relations and the loss of moral order. Given this scenario, crime rates are high and cause the rupture of the instruments of social control that lead to social disorganization. An empirical research, carried out with papers published in annals and journals of Geography and other applied social sciences, was crucial for the discussion of the theme of this thesis, supporting a survey of evidence on the relationship between crimes and socio-spatial determinants. Through descriptive research, with secondary data, it was observed that the RIDE/DF was subjected to a disorderly urbanization not related primarily to industrialization nor directly linked to factors tied to egalitarian regional development, since it was created on the basis of centralized political decisions, which to this day, still causes problems regarding its definition as a region of development, governance, funds, mapping of local flows and demands, active participation of federated entities and civil society etc. This situation resulted in several problems, such as structural unemployment, housing deficit, urban violence and socio-spatial inequality, which generated spillover effects for the municipalities that comprise it. In these circumstances, this thesis sought to answer the following propositions: how is the Geography of criminality configured in RIDE/DF, interpreted through the analysis of the spatialization of crimes against the person in the period from 2010 to 2017, and crimes against property from 2017 to 2018? Can this criminality be explained by socio-spatial variables and phenomena? Were there spillovers of crimes among the federated entities of this region in the period under review? Through descriptive and quantitative research, using secondary data, it was possible to conclude that the crime rates in RIDE/DF were not randomly distributed in space since , by means of an exploratory analysis of spatial data, the existence of spatial dependency was detected, in which the municipalities bordering and closer to the DF concentrate the highest crime rates, being those responsible for more than 80% of the records of crimes occurred within the period under analysis. The main victims are young, black men shot by firearms, and the proportion of young population between 15 and 19 years of age was a determining factor of positive correlation, among other significant conditions obtained by estimations of spatial regression models through the Spatial Durbin Model - SDM. In the analysis of the effects, it was noted that in crimes against life there was a significant presence of spillovers, around 51% of the total effects. While in crimes against property the direct or own effects of each municipality were more preponderant than the indirect effects or spillovers of neighbors that represented only 22% of the total effects.